SPASTICITY - Rahşan Kamiloğlu; Ayşe Bilgiç (Archives of Rheumatology, 2002)
Spasticitiy is one of the most important disporders in people with disease of central nervous system. It is a motor neuron disorder which is a component of upper motor neuron syndrom and results from hyperexcitability of stretch reflexes characterized by an increased muscle tone. A variety of diseases which damage descending motor pathways at cortical or subcortical levels, brainstem or spinal cord may cause spasticity. Among these disease are stroke, degerenative lesions, multiple sclerosis, brain injuries due to trauma, cerebral palsy, spinal cord injuries, space-occupying lesions and transverse myelitis.